Uniformly sodium ions doped LiNi0.84Co0.11Mn0.05O2 cathode material with high performance for lithium-ion batteries. (1st May 2023) - Liu, Jiuqing; Jiao, Wen; Wang, Xu; Mao, Gaoqiang; Yao, Yu; Yu, Wanjing; Tong, Hui
Abstract: Nickel-rich ternary cathode material is widely used in various fields due to its superior operating voltage and theoretical specific capacity. However, the nickel-rich cathode material undergoes cation mixing in highly delithiated state, which leads to rapid capacity decay and poor cycling stability. In this study, sodium ions were uniformly doped into the nickel-rich cathode material (Na-LNCM) using a hydrothermal method to overcome the problems mentioned above. Na-LNCM exhibits better cycling and rate performance, and lower electrochemical polarization compared with those of pristine material. The specific capacity of the Na-LNCM material was 138.3 mAh∙g −1 at 10 C current density, and the capacity retention ratio was 82.9% after 100 cycles at 1 C. The apparent enhancement in electrochemical performances is attributed to the truth that sodium ions occupy Li sites in the Li slab, which can broaden Li layer spacing, widen the diffusion channels of Li +, reduce cation mixing, and support the crystal structure of nickel-rich ternary cathode material. Moreover, compared with other methods, the doped sodium ions can be distributed more uniformly by the hydrothermal method, which could further enhance the electrochemical performance of the cathode material.